Achieving visible light-driven hydrogen evolution at positive bias with a hybrid copper–iron oxide|TiO2-cobaloxime photocathode. Issue 10 (30th April 2020) - Tapia, C.; Bellet-Amalric, E.; Aldakov, D.; Boudoire, F.; Sivula, K.; Cagnon, L.; Artero, V.
Abstract : H2 is an environmentally-friendly fuel that would allow for a circular economy but its sustainable production from solar energy and water using stable, efficient and scalable Earth-abundant materials, remains a challenge. Abstract : H2 is an environmentally-friendly fuel that would allow for a circular economy but its sustainable production, e.g. from solar energy and water, remains a challenge. A hybrid CuFe x O y |TiO2 -CoHEC (CoHEC = chloro([4, 4′-bipyridine]-2, 6-dicarboxylic acid)bis(dimethylglyoximato)cobalt(iii )) photocathode for hydrogen evolution reaction (HER), with faradaic efficiencies of 54–88%, is described, the preparation of which uses only non-toxic and Earth-abundant elements, avoids etching treatments and limits the use of organic solvents. The semi-conducting CuFe x O y light absorber is obtained by sol–gel synthesis followed by calcination at moderate temperature. Grafting the CoHEC cobaloxime catalyst at its surface results in H2 evolution with an onset photocurrent potential of +860 mV; this process being stabilized by the presence of a thin layer of amorphous TiO2 deposited onto CuFe x O y .